EFEKTIVITAS PERAWATAN LUKA OPERASI DENGAN TEKNIK NEGATIVE PRESSURE WOUND THERAPY (NPWT) PADA PASIEN POST-LAPAROTOMI DI RUMAH SAKIT KOTA PADANG - sari, Indah kumala; Sandra, Rhona; morika, honesty diana; Sari, Putri Minas; nur, siti aisyah (E-Jurnal Medika Udayana, 2024)
Surgical wound infection is a common risk for patients following surgery. Proper and effective treatment is necessary to prevent complications and expedite the healing process. Negative Pressure Wound Therapy (NPWT) is one of the modern treatment methods used to care for surgical wounds. This research aims to evaluate the effectiveness of NPWT in the treatment of surgical wounds in post-laparotomy patients at Padang City Hospital. This study is a quasi-experimental research. The research sample consists of 16 post-laparotomy patients treated at Padang City Hospital who received NPWT treatment during the study period. The research results show that NPWT is effective in improving the surgical wound healing process in post-laparotomy patients. Patients treated with NPWT experienced a reduced healing time for their wounds and a decreased risk of infection. The research results also indicate that the use of NPWT can reduce patient care costs. In this regard, the research findings demonstrate that NPWT can provide significant benefits in the care of post-laparotomy patients. However, it's important to note that NPWT is not the sole effective treatment method. The appropriate treatment should be chosen based on the patient's condition and the severity of the wound. Overall, this research indicates that NPWT is an effective treatment method for surgical wound care in post-laparotomy patients. Nevertheless, further research is needed to ensure the effectiveness of this technique in a broader population. Keywords: Surgical Wound Care, Negative Pressure Wound Therapy (NPWT), Post-Laparotomy.